Las fantásticas aventuras de Los Cinco 3 = The famous five 3 = Los Cinco 3 - Kysh, Tony; Blyton, Enid, 1897-1968; Price, John; Hart, Paul; Williamson, Marco; Dixon, Dave; Campbell, Joe; Rooper, Jemima; Child, Paul; Seymour, Alan; Cresswell, Helen, 1936-2005; Jones, Julia, 1923-2015 (Filmax Home Video, 2003)
Serie de TV que adapta las famosas aventuras de Los Cinco